Safety and efficacy of cardioneuroablation for vagal bradycardia in a single arm prospective study - Han, Yafan; Shao, Mingliang; Yang, Hang; Sun, Huaxin; Sang, Wanyue; Wang, Lu; Wang, Liang; Yang, Suxia; Jian, Yi; Tang, Baopeng; Li, Yaodong (Scientific reports, 2024)
Cardioneuroablation (CNA) is currently considered as a promising treatment option for patients with symptomatic bradycardia caused by vagotonia. This study aims to further investigate its safety and efficacy in patients suffering from vagal bradycardia. A total of 60 patients with vagal bradycardia who underwent CNA in the First Affiliated Hospital of Xinjiang Medical University from November 2019 to June 2022. Preoperative atropine tests revealed abnormal vagal tone elevation in all patients. First, the electroanatomic structures of the left atrium was mapped out by using the Carto 3 system, according to the protocol of purely anatomy-guided and local fractionated intracardiac electrogram-guided CNA methods. The upper limit of ablation power of superior left ganglion (SLGP) and right anterior ganglion (RAGP) was not more than 45W with an ablation index of 450.Postoperative transesophageal cardiac electrophysiological examination was performed 1 to 3 months after surgery. The atropine test was conducted when appropriate. Twelve-lead electrocardiogram, Holter electrocardiogram, and skin sympathetic nerve activity were reviewed at 1, 3, 6 and 12 months after operation. Adverse events such as pacemaker implantation and other complications were also recorded to analyze the safety and efficacy of CNA in the treatment of vagus bradycardia. Sixty patients were enrolled in the study (38 males, mean age 36.67 ± 9.44, ranging from 18 to 50 years old). None of the patients had a vascular injury, thromboembolism, pericardial effusion, or other surgical complications. The mean heart rate, minimum heart rate, low frequency, low/high frequency, acceleration capacity of rate, and skin sympathetic nerve activity increased significantly after CNA. Conversely, SDNN, PNN50, rMSSD, high frequency, and deceleration capacity of rate values decreased after CNA (all P < 0.05). At 3 months after ablation, the average heart rate, maximum heart rate, and acceleration capacity of heart rate remained higher than those before ablation, and the deceleration capacity of heart rate remained lower than those before ablation and the above results continued to follow up for 12 months after ablation (all P < 0.05). There was no significant difference in other indicators compared with those before ablation (all P > 0.05). The remaining 81.67% (49/60) of the patients had good clinical results, with no episodes of arrhythmia during follow-up. CNA may be a safe and effective treatment for vagal-induced bradycardia, subject to confirmation by larger multicenter trials.